테트라부틸암모늄 브로마이드 기반 소수성 공융용매를 이용한 강황(Curcuma longa L.)의 curcuminoids 추출 - 김현호(Hyeonho Kim); 조윤진(Yunjin Cho); 이윤열(Yunyeol Lee); 남태규(Tae Gyu Nam) (한국식품과학회지, 2024)
본 연구에서는 강황 curcuminoids를 HDES를 사용하여 추출하였다. 실험한 HDES 혼합물 중 TBAB와 capric acid를 1:3의 몰비율로 혼합한 HDES가 가장 우수한 추출 효율을 보였다. 중심합성계획법을 이용하여 HDES (TC13)의 최적 추출 조건을 얻었으며, 추출 시간과 추출 온도의 상관관계를 파악하였다. 회귀 모델과 분산분석을 통해 모델의 정확성과 신뢰성을 검증하였으며, 최적 추출조건에서 실험 결과와의 유의차를 확인하였다. 또한 FTIR분석을통하여 TC13의 HDES 형성을 확인하였다. TC13을 이용한 강황 curcuminoids의 추출은 기존 유기용매를 대체하는 친환경적인 요소와 함께 보다 높은 추출 효율을 나타냈다. 본 연구는 제약, 천연 색소 및 식품 산업에 이용될 수 있는 c u rcu minoid 를 효율적이며 친환경적으로 추출하기 위한 방법으로 TBAB기반HDES의 사용가능성을 제시하였다. For sustainable green chemistry, deep eutectic solvents (DESs) have attracted growing interest as alternatives to organic solvents. This study investigated a methodology for extracting curcuminoids from turmeric using hydrophobic DESs. Tetrabutylammonium bromide:capric acid DES at a 1:3 molar ratio exhibited the best extraction yield of curcuminoids. The physical properties and chemical structure of the selected hydrophobic DES was studied. The extraction conditions for bisdemethoxycurcumin (BDC), desmethoxycurcumin (DTC), and curcumin (CUR) were optimized using the central composite design and response surface methodology. The optimal extraction temperature and time were 13.6 min at 44.3oC for BDC, 13.4 min at 45.7oC for DTC, and 12.1 min at 59.8oC for CUR. Based on these finding, the developed method using a hydrophobic DES could be regarded as a sustainable, eco-friendly, highly efficient, and green approach for curcuminoid extraction. DES is expected to be useful in industrial environments as it is eco-friendly and has higher extraction efficiency than that of conventional organic solvents. KCI Citation Count: 0